2014
DOI: 10.1371/journal.pone.0093179
|View full text |Cite
|
Sign up to set email alerts
|

SCO-Spondin Derived Peptide NX210 Induces Neuroprotection In Vitro and Promotes Fiber Regrowth and Functional Recovery after Spinal Cord Injury

Abstract: In mammals, the limited regenerating potential of the central nervous system (CNS) in adults contrasts with the plasticity of the embryonic and perinatal periods. SCO (subcommissural organ)-spondin is a protein secreted early by the developing central nervous system, potentially involved in the development of commissural fibers. SCO-spondin stimulates neuronal differentiation and neurite growth in vitro. NX210 oligopeptide was designed from SCO-spondin's specific thrombospondin type 1 repeat (TSR) sequences th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 62 publications
0
32
0
Order By: Relevance
“…SSPO, an evolutionarily conserved gene in the central nervous systems of chordates, has a neuroprotective effect by promoting neuronal differentiation and growth in spinal cord injuries. 46 , 47 Our results showed that the downregulation of SSPO could be triggered by LPS infection in amphioxus. Therefore, we propose that the differential expression of these key neuro-related genes may be involved in neuro-inflammation, implying that a rudimentary, active neuro-immune system probably existed in basal chordates and acted as an ancient immune system in the ancestor of vertebrates.…”
Section: Discussionmentioning
confidence: 54%
“…SSPO, an evolutionarily conserved gene in the central nervous systems of chordates, has a neuroprotective effect by promoting neuronal differentiation and growth in spinal cord injuries. 46 , 47 Our results showed that the downregulation of SSPO could be triggered by LPS infection in amphioxus. Therefore, we propose that the differential expression of these key neuro-related genes may be involved in neuro-inflammation, implying that a rudimentary, active neuro-immune system probably existed in basal chordates and acted as an ancient immune system in the ancestor of vertebrates.…”
Section: Discussionmentioning
confidence: 54%
“…The homologous segment contains vWFD, C8, TIL and LDLrA domains, while the remainder features numerous copies of TSP-1, SCO-spondin region repeats (SCOR), TIL and a CTCK [ 76 ]. Interestingly, the TSP-1-rich segment from SCO-spondin that is absent in P-vulgata_3 is specifically implicated in promoting neuronal development [ 82 , 83 ], which appears to be a superfluous function for adhesive proteins. Furthermore, in situ hybridization localized P-vulgata_3 expression to the pedal sole, ruling out contamination as a possible source of SCO-spondin-like peptides.…”
Section: Discussionmentioning
confidence: 99%
“…SCO-spondin is expressed in the subcommissural organ (SCO) and plays a role in neuronal development [ 51 ]. It also promotes commissural fiber regrowth and functional recovery after spinal cord injury [ 52 ]. The DNA polymerase ε catalytic subunit encoded by Pole contributes to DNA repair and chromosomal DNA replication [ 33 ].…”
Section: Discussionmentioning
confidence: 99%